The ecology of law : toward a legal system in tune with nature and community - Capra, Fritjof; Mattei, Ugo (Berrett-Koehler Publishers, 2015)
Extraordinary author team: Fritjof Capra is the bestselling author of The Tao of Physics and The Web of Life, and Ugo Mattei is a distinguished professor holding chairs at Hastings College of the Law and the University of Turin. Pioneering work: This is the first book to explore the historical connections between natural science and jurisprudence, to illuminate how law's failure to keep pace with science is behind a host of modern problems, and to offer a solution. At the root of many of the environmental, economic, and social crises we face today is a legal system based on an outdated worldview. In this groundbreaking book, bestselling author, physicist, and systems theorist Fritjof Capra and distinguished legal scholar Ugo Mattei show how, by incorporating concepts from modern science, the law can become an integral part of bringing about a better world. This is the first book to trace the fascinating parallel history of law and science from antiquity to modern times, showing how the two disciplines have always influenced each other--until recently. In the past few years, the scientific paradigm has shifted dramatically, from seeing the natural world as a kind of cosmic machine to understanding it as a network of fluidly interacting communities. But law is stuck in a mechanistic, seventeenth-century view that the world is made up of discrete individual parts. This has led to legal theory focusing on these parts and ignoring the bigger picture--for example, elevating the rights of individual property owners over the good of the community. But Capra and Mattei outline the basic concepts and structures of a legal order consistent with the ecological principles that sustain life on this planet. This is a profound and visionary reconceptualization of the very foundations of the Western legal system, with profound implications for the future of our planet.